Cerium oxide loaded with Gum Arabic as environmentally friendly anti-corrosion additive for protection of coated steel - Muddasir Nawaz (17052438) (2021)
The depreciation of assets and safety threats because of corrosion has forced to develop eco-friendly and smarter corrosion protection strategies. In this study, natural Gum Arabic (GA) was used as a corrosion inhibitor and loaded into cerium oxide nanoparticles (CONPs) to develop an environment-friendly additive for corrosion protection of coated steel in the marine environment. This additive was uniformly dispersed into an epoxy formulation that was used to protect steel plates. Epoxy coatings containing CONPs, without GA, were also prepared as reference. High-Resolution Transmission Electron Microscopy (HR-TEM) and Fourier Transform infrared spectroscopy (FTIR) revealed the successful loading of GA into the CONPs. Thermogravimetric analysis (TGA) and Brunauer-Emmett-Teller (BET) techniques confirmed approximately ⁓30.0 wt% loading of GA into the CONPs. Electrochemical impedance spectroscopy (EIS) demonstrated the anticorrosion properties of the epoxy coatings modified with the GA loaded CONPs when compared to reference coatings. The corrosion protection mechanism postulates that GA loaded CONPs act as a filler material for epoxy coating and it can also aid the recovery of the protective properties of the epoxy coating leading to the formation of a stable protective layer. Other Information Published in: Materials & Design License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.matdes.2020.109361